Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-41191-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of Circulating YKL-40 Levels and CHI3L1 Variants with the Risk of Spinal Deformity Progression in Adolescent Idiopathic Scoliosis

Abstract: The cellular and molecular mechanisms underlying spinal deformity progression in adolescent idiopathic scoliosis (AIS) remain poorly understood. In this study, 804 French-Canadian patients and 278 age- and sex-matched controls were enrolled and genotyped for 12 single nucleotide polymorphisms (SNPs) in the chitinase 3-like 1 ( CHI3L1 ) gene or its promoter. The plasma YKL-40 levels were determined by ELISA. We showed that elevation of circulating YKL-40 levels was correlated with a reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Adolescent idiopathic scoliosis (AIS) manifests as a three-dimensional (3D) deformity of the spinal column that occurs around puberty. Several factors such as genetics 1,2 , biomechanics 3 , morphology of the vertebral bones, intervertebral disc, and muscle physiology 49 , hormones 10,11 , environmental factors 12,13 , and neural system deficiencies 14,15 are considered as the underlying cause of the spinal deformity in AIS. While each of these factors explained part of the pathogenesis of this disease, none have proved to be its main or primary cause.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescent idiopathic scoliosis (AIS) manifests as a three-dimensional (3D) deformity of the spinal column that occurs around puberty. Several factors such as genetics 1,2 , biomechanics 3 , morphology of the vertebral bones, intervertebral disc, and muscle physiology 49 , hormones 10,11 , environmental factors 12,13 , and neural system deficiencies 14,15 are considered as the underlying cause of the spinal deformity in AIS. While each of these factors explained part of the pathogenesis of this disease, none have proved to be its main or primary cause.…”
Section: Introductionmentioning
confidence: 99%
“…Dina Nada et al investigated the relationship of circulating YKL-40 levels and CHI3L1 variants with the risk of progression of scoliosis to spinal deformity in adolescent idiopathic scoliosis. It has been shown that the rs880633 polymorphism of the CHI3L1 gene is positively correlated with high YKL-40 levels and is protective against spinal deformity 14 . Huang et al examined the polymorphisms of the CHI3L1 gene in patients with hepatocellular cancer and found a high rate of CHI3L1rs880633 polymorphism in patients with hepatocellular cancer 15 .…”
Section: Discussionmentioning
confidence: 99%